Use of Pentoxifylline combined with captopril/losartan in hypertensive or diabetic patients: An integrative review of randomized clinical trials (Research, Society and Development, 2023)
Objective: To perform an integrative literature review to analyze the effects of the use of Pentoxifylline (PTX) combined and/or compared to captopril or losartan. Methodology: An integrative literature review was performed analyzing randomized clinical trials in Portuguese, English and Spanish in the following databases: MEDLINE via PubMed and Cochrane. The descriptors used were "Pentoxifylline", "Losartan", "Captopril", "Arterial Pressure" and "Hypertension, Malignant" according to the DeCS, with 6 randomized studies at the end. Results: Several studies point to the positive effects of PTX when associated with captopril or losartan with regard to renal function in hypertensive and/or diabetic patients. The literature is still uncertain and the data contradict each other regarding the effects on the blood pressure of patients when receiving the addition of PTX or in comparison of PTX versus losartan or captopril. Conclusion: The literature and clinical trials are still divergent regarding the effects on blood pressure, although there is a consensus regarding its positive effects on proteinuria. Randomized clinical trials analyzing the direct comparative effect between drugs are needed. Meta-analyses are necessary to make quantitative analysis of the studies already available.